Exploring Post-Incarceration Residential Trajectories: Indicators of Housing Stability during the Re-Entry Process. Issue 3 (27th May 2021) - Walter, Rebecca J.; Caudy, Michael; Galvan Salcido, Christine; Ray, James; Viglione, Jill
ABSTRACT: Extant research on housing instability focuses on external housing barriers but limited research exists on individual-level indicators of housing stability for individuals returning to society from incarceration. This study addresses this gap with data collected from 70 individuals recently released from incarceration who returned to Bexar County (San Antonio, Texas) that were not placed in specific housing programmes, leaving them to seek housing independently. The study explores residential trajectories and the utility of individual-level characteristics, specifically readiness for change, in relation to housing stability. The findings reveal the importance of assessing the dynamics of each individual living situation since many of the participants are housed but not in stable housing situations. Furthermore, readiness for change (specifically action, self-sufficiency, and human agency) is found to be a significant indicator of housing stability and may represent an important intervention target for re-entry and reintegration programmes.